PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 0 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Amnah Amnah; Eddy Noviana; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is begin from the low of the social studies students learning outcomes with an average grade 56,25 while the score of minimum criteria of completeness (KKM) is 65. This research is classroom action research (CAR). That suppose to increase the social studies student learning outcomes at three grade of SD Negeri 008 Sungai Segajah Kecamatan Kubu Kabupaten Rokan Hilir. The formulation of the research is does the application of cooperative learning model type make a match to increase the students learning outcomes of social student at three grade of SD Negeri 008 Sungai Segajah Kecamatan Kubu Kabupaten Rokan Hilir. The data was collected by using observation paper. And god the result by examination I and II. The value before CAR by individual are 16 students (80%) that passed with average 66. And in cycle II that passed are 17 students or (85%) with average passed 70,5. So the improvement of students learning out comes from the bassed score to cycle I increase about 41,33% whereas from based score to cycle II increase about 25,33%. The activity of the teacher in first cycle with average 58,33% and in second cycle about 83,33%. The student is activity in first cycle is average about 54,16% and the scond cycle is everage 79,16%. The result of this research said that the application of cooperative learning model type make a match can increase the social studies students learning outcomes at three grade of SD Negeri 008 Sungai Segajah Kecamatan Kubu Kabupaten Rokan HilirKeywords : make a match, social studies outcomes